Symmetric dimeric adamantanes for exploring the structure of two viroporins: influenza virus M2 and hepatitis C virus p7 - Mandour YM; Breitinger U; Ma C; Wang J; Boeckler FM; Breitinger HG; Zlotos DP (Dove Medical Press, 2018)
Yasmine M Mandour,1 Ulrike Breitinger,2 Chunlong Ma,3 Jun Wang,3 Frank M Boeckler,4 Hans-Georg Breitinger,2 Darius P Zlotos1 1Department of Pharmaceutical Chemistry, German University in Cairo, 2Department of Biochemistry, The German University in Cairo, Cairo, Egypt; 3Department of Pharmacology and Toxicology, University of Arizona, Tucson, AZ, USA; 4Department of Pharmaceutical and Medicinal Chemistry, Eberhard Karls University of Tübingen, Tübingen, Germany Background: Adamantane-based compounds have been identified to interfere with the ion-channel activity of viroporins and thereby inhibit viral infection. To better understand the difference in the inhibition mechanism of viroporins, we synthesized symmetric dimeric adamantane analogs of various alkyl-spacer lengths.Methods: Symmetric dimeric adamantane derivatives were synthesized where two amantadine or rimantadine molecules were linked by various alkyl-spacers. The inhibitory activity of the compounds was studied on two viroporins: the influenza virus M2 protein, expressed in Xenopus oocytes, using the two-electrode voltage-clamp technique, and the hepatitis C virus (HCV) p7 channels for five different genotypes (1a, 1b, 2a, 3a, and 4a) expressed in HEK293 cells using whole-cell patch-clamp recording techniques.Results: Upon testing on M2 protein, dimeric compounds showed significantly lower inhibitory activity relative to the monomeric amantadine. The lack of channel blockage of the dimeric amantadine and rimantadine analogs against M2 wild type and M2-S31N mutant was consistent with previously proposed drug-binding mechanisms and further confirmed that the pore-binding model is the pharmacologically relevant drug-binding model. On the other hand, these dimers showed similar potency to their respective monomeric analogs when tested on p7 protein in HCV genotypes 1a, 1b, and 4a while being 700-fold and 150-fold more potent than amantadine in genotypes 2a and 3a, respectively. An amino group appears to be important for inhibiting the ion-channel activity of p7 protein in genotype 2a, while its importance was minimal in all other genotypes.Conclusion: Symmetric dimeric adamantanes can be considered a prospective class of p7 inhibitors that are able to address the differences in adamantane sensitivity among the various genotypes of HCV. Keywords: adamantane, dimers, viroporins, p7, M2, HCV